OPTIMIZING PASSPORT SERVICES SOCIALIZATION AT IMMIGRATION OFFICE CLASS I BANDUNG USING FISHBONE METHOD FOR ENHANCED EFFECTIVENESS - Budy Mulyawan; Muammar Ricky Putra (Jurnal Abdimas Imigrasi, 2023)
Effective implementation of socializing passport services at the Bandung Class I Immigration Office is a complex challenge. In an effort to overcome this problem, the Fishbone method is used to identify root causes and design appropriate solutions. Through in-depth analysis, various factors such as people, process, technology, environment, and policies were identified as contributing to effectiveness in conveying information to the public. The results of this analysis form the basis for corrective actions, such as training immigration officers, streamlining procedures, increasing use of social media, and increasing access to information. Thus, the Fishbone method provides strong and systematic insights in improving the socialization of passport services, supporting immigration offices in facing challenges, and optimizing the community's experience.